Morphological Aspects of Absorption of Antibodies - N. Shulga, Nikolay; M. Mandro, Nikolay; A. Gavrilova, Galina; N. Chubin, Alexey; Yu. Sayapina, Irina; A. Gavrilov, Yuriy; V. Hibchenov, Lopsondorzho; V. Trush, Natal'ya (International Journal of Engineering and Technology, 2018)
Placenta, depending on the species histological features, may interfere or promote the transmission of antibodies in the mother-fetus system. There are several types of placentas: epithelial type (horses, donkeys and pigs), desmochoric type (cows, sheep and goats), endothelial type (rabbits, Guinea pigs), hemochorial type (monkeys and women). Desmochoric Â and epithelial type of the placenta block the transfer of circulating maternal antibodies to the fetus. In animals with these types of placentae transfer of maternal antibodies to offspring is carried out by colostrum. Hemochorionic and endothelial chorionicÂ placentae provides active transport of antibodies from the mother's bloodstream into the bloodstream of the fetus. Therefore, newborns have a complete set of maternal antibodies. The aim of our study was to investigate the mechanism of absorption of antibodies from colostrum by the epithelial cells of the small intestine of newborn animals with epithelial Â and desmochoric Â types of placentas. The article presents the results of the absorption of antibodies by epithelial cells of the small intestine of newborn animals with colostrum - type transmission of immune proteins from mother-offspring.Â Thus, it was established that the absorption of antibodies by epithelial cells of the small intestine is limited in time (24-72 hours). The mechanism of absorption is the fetal structure of the epithelial cells of the small intestine with the ability to absorb antibodies, and the termination of antibody absorption is associated with the replacement of fetal enterocytes by postnatal ones.Â